2016
DOI: 10.1016/j.chembiol.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Protein-Protein Interaction Inhibitor of Oncogenic Rho Signaling

Abstract: Uncontrolled activation of Rho signaling by RhoGEFs, in particular AKAP13 (Lbc) and its close homologs, is implicated in a number of human tumors with poor prognosis and resistance to therapy. Structure predictions and alanine scanning mutagenesis of Lbc identified a circumscribed hot region for RhoA recognition and activation. Virtual screening targeting that region led to the discovery of an inhibitor of Lbc-RhoA interaction inside cells. By interacting with the DH domain, the compound inhibits the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Such protein interfaces could be targeted by peptides or small molecule compounds to inhibit cardiac fibrosis. In this respect, two studies recently identified small molecules inhibiting the ability of AKAP13 to bind and activate RhoA [155,174]. It will be crucial to determine whether such molecules can efficiently inhibit the pro-fibrotic function of the AKAP-Lbc/RhoA pathway both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such protein interfaces could be targeted by peptides or small molecule compounds to inhibit cardiac fibrosis. In this respect, two studies recently identified small molecules inhibiting the ability of AKAP13 to bind and activate RhoA [155,174]. It will be crucial to determine whether such molecules can efficiently inhibit the pro-fibrotic function of the AKAP-Lbc/RhoA pathway both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This anchoring protein coordinates multiple signaling enzymes, such as PKA, protein kinase Cη (PKCη), protein kinase D1 (PKD1), PDE4D, phosphatases, and various MAPKs involved in the cardiac adaptation to stress and damage [148][149][150][151][152][153][154]. Unlike other AKAPs, AKAP13 also contains tandem Dbl homology (DH) and pleckstrin homology (PH) domains, which confer to the protein GEF activity towards RhoA and RhoC [146,155]. AKAP13 RhoGEF activity can be regulated bidirectionally by activating or inhibitory signals.…”
Section: Akap13mentioning
confidence: 99%
“…Immune related disorders, Alzheimer's disease (Nishikimi et al, 2012) LARG Y16 Cell-free assay, Cell culture Accute myeloid Leykemia (Shang et al, 2013) Lbc A13 Cell-free assay, Cell culture Various cancers (Diviani et al, 2016) (a) The inhibitor of Dock5 (CAS 54129-15-6) should not be mistaken for the inhibitor of the protein arginine methyltransferase PRMT1 (CAS 1229236-78) and for the non-peptide selective AT2 receptor agonist M24 (CAS 477775-14-7), which were also named C21.…”
Section: Trio (D1) Itx3mentioning
confidence: 99%
“…Y16 does not bind to Lbc, another RGS-RhoGEFs closely related to LARG. A model for the RhoA-Lbc complex was built by structural analogy after the RhoA-LARG complex and the aminoacids involved in the interaction between the RhoA and Lbc were deduced (Diviani et al, 2016). A virtual screening on the ZINC database highlighted 30 compounds likely to interfere with the formation of the RhoA-Lbc complex.…”
Section: Rational Designmentioning
confidence: 99%
“…approaches have led to molecules with severe selectivity issues (24). From the purely molecular point of view, a few key studies have described the relationship between RhoA and GEF11 or GEF12 (25)(26)(27)(28), but little is known regarding the interface between RhoA and Net1.…”
mentioning
confidence: 99%